El sistema de salud argentino: un análisis a partir del acceso a los medicamentos - Marin, Gustavo Horacio (2021)
The objective of the work is to describe features of the health system in Argentina though the way that the population access to medicines. Argentine health system reflects all the systems of the world in just one country. The National Public Health system, the Social Security and Private sectors coexist in order to attend the needs and demand of the population. Medicines are good examples to analyze how the system works. This text provides a description of each health sub-sectors in Argentina, and performs an analysis on the differences in access to medicines that patients have. Finally, it is propose recommendations for the health system to improve equity in terms of population access to medicines.